Complementary Therapies for Osteoarthritis: Are They Effective? - Shengelia, Rouzi (2012)
Increasing interest has focused on complementary management modalities, including Tai chi, acupuncture, yoga, and massage therapy as treatments for osteoarthritis (OA). This review article synthesizes evidence from randomized controlled trials (RCTs) and systematic reviews (SRs) that examined one or more of the above as treatments for OA. Medline, PubMed, and CINAHL databases were searched to identify English-language articles employing an RCT design or that conducted a SR of published studies and presented data on symptom or functional outcomes. Two authors independently abstracted relevant information (e.g., study sample, intervention characteristics, treatment effects, safety data). Retained articles (N=29) included those that evaluated tai chi (8 RCTs; 2 SRs); acupuncture (11 RCTs; 4 SRs); yoga (2 RCTs); and massage therapy (2 RCTs). Available evidence indicates that Tai chi, acupuncture, yoga, and massage therapy are safe for use by individuals with OA. Positive short-term (6 months or less) effects in the form of reduced pain and improved self-reported physical functioning were found for all 4 treatments. Limited information exists regarding the relative effectiveness of the therapies (e.g., yoga vs. Tai chi vs. acupuncture), as well as treatment effects in persons with joint involvement besides the knee and in distinct (e.g., older vs. younger adults, persons with mild vs. moderate vs. advanced disease) patient subgroups. Complementary therapies can reduce pain and improve function in adults with OA. Research is needed to evaluate long-term benefits of the treatments, as well as their relative effects among diverse patient subgroups.